Integration of metabolomics, genomics, and immune phenotypes reveals the causal roles of metabolites in disease - Chu, Xiaojing; Jaeger, Martin; Beumer, Joep; Bakker, Olivier B.; Aguirre-Gamboa, Raul; Oosting, Marije; Smeekens, Sanne P.; Moorlag, Simone; Mourits, Vera P.; Koeken, Valerie A. C. M.; de Bree, Charlotte; Jansen, Trees; et al. (Genome Biology, 2021)
Recent studies highlight the role of metabolites in immune diseases, but it remains unknown how much of this effect is driven by genetic and non-genetic host factors. We systematically investigate circulating metabolites in a cohort of 500 healthy subjects (500FG) in whom immune function and activity are deeply measured and whose genetics are profiled. Our data reveal that several major metabolic pathways, including the alanine/glutamate pathway and the arachidonic acid pathway, have a strong impact on cytokine production in response to ex vivo stimulation. We also examine the genetic regulation of metabolites associated with immune phenotypes through genome-wide association analysis and identify 29 significant loci, including eight novel independent loci. Of these, one locus (rs174584-FADS2) associated with arachidonic acid metabolism is causally associated with Crohn's disease, suggesting it is a potential therapeutic target. This study provides a comprehensive map of the integration between the blood metabolome and immune phenotypes, reveals novel genetic factors that regulate blood metabolite concentrations, and proposes an integrative approach for identifying new disease treatment targets.